2012
DOI: 10.1115/1.4005815
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Combustor-Turbine Interaction Using an Isothermal, Nonreacting Tracer

Abstract: Understanding the interaction between the combustor and turbine subsystems of a gas turbine engine is believed to be key in developing focused strategies for improving turbine performance. Past studies have approached the problem starting with an existing turbine rig with inlet conditions provided by "representative" hardware which attempts to mimic some key flow features exiting the combustor. In this paper, experiments are performed which center around complete engine hardware of the combustor, including eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Cha et al [8] have investigated the migration of the burner core using a passive CO 2 tracer, which was fed through the fuel injectors into the combustor. They determined a pronounced concentration profile at the turbine inlet, resembling a hot streak location.…”
Section: Tracing Of Turbomachinery Flowsmentioning
confidence: 99%
“…Cha et al [8] have investigated the migration of the burner core using a passive CO 2 tracer, which was fed through the fuel injectors into the combustor. They determined a pronounced concentration profile at the turbine inlet, resembling a hot streak location.…”
Section: Tracing Of Turbomachinery Flowsmentioning
confidence: 99%
“…The level of swirl normally present in an aeroengine RQL combustor was presumed to be negligible relative to the effect of high-momentum flux dilution injection. The study by Cha et al [15] for a similar RQL geometry also indicated little effect of upstream swirl on dilution jet trajectory.…”
Section: Methodsmentioning
confidence: 77%
“…Another potential issue from performing separate simulations is the absence of the vane's impact in the combustor simulation; this is especially true for combustors with dilution jets positioned near the turbine inlet. Cha et al [15] showed through experimental and computational studies that the nozzle guide vane's (NGV) potential field has an effect on the upstream combustor flow. Cha et al found that the NGV's impact occurs well before the combustor-turbine interaction plane where many combustor-only studies end.…”
Section: Relevant Literaturementioning
confidence: 99%
“…This is then delivered to the vertically mounted test section through a bell-mouthed inlet and honeycomb flow straightener. The test facility is able to operate a 1.5 stage axial flow compressor to deliver pre-diffuser flow structures that are representative of the engine environment (Cha et al 2012). For these tests, however, the compressor rotor was replaced with a pre-swirl vane row, designed to replicate the approach flow angle provided to the outlet guide vane row by the rotor.…”
Section: Introductionmentioning
confidence: 99%